Transformation and Future Challenges of Islamic Law in Indonesia - Siroj, A. Malthuf; Marzuki, Ismail; Elkhairati, Elkhairati (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
This study aims to investigate the transformation of Islamic law starting from pre-entry of Islam to Indonesia, entry of Islam, colonialism, and independence to current reformation in Indonesia, as well as various challenges to the formalization of Islamic law. The method used was a qualitative method with the type of library research namely by researching and reviewing legal materials that include primary legal materials, secondary legal materials, and tertiary legal materials that relevant to the object of this research. The results show that pre-entry of Islam to Indonesia, the applicable law was adat law, then since the entry of Islam into Indonesia, Islamic law has been well accepted and implemented by the community, and even its existence has gained legitimacy from both legal experts and the Dutch government. After Indonesia's independence, especially during the Old Order era, Islamic law did not transform significantly. During the New Order after such party collapsed, Islamic law began to transform significantly. Although since the reform period, Islamic law has transformed significantly, the challenges of Islamic law are serious, both internal and external. The most dominant internal challenges among are not fully codified Islamic law, Indonesian pluralistic condition, politics of the rulers' law, misconceptions of some legal experts about Islamic law, and other. Meanwhile, external challenges include influence of transnational ideologies which give a negative stigma against Islam, the development of Western ideologies that clash with Islamic law and the human rights, and strong influence of the domination of Western law in Indonesia.